Forensic investigations and risk management in mobile and wireless communications - Sharma, Kavita 1985-; Makino, Mitsunori; Shrivastava, Gulshan 1987-; Agarwal, Basant (IGI Global, 2020)
"This book examines mobile forensics and analytics, network security, computer science, security engineering, and forensic computing"--